A SPIRITUAL APPROACH TO HANDLING COLLEGE STUDENT MENTAL HEALT PROBLEMS AFTER THE PANDEMIC AT LK3 UIN JAKARTA - Kharima, Nadya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
College Students always experience ups and downs in managing their lives, both as College students and as children in their families and social environment. Not to mention the adaptation of the learning process which is quite fast, from the pandemic to the changes after the pandemic. So it becomes a natural thing that during their study period, it is not uncommon for College students to experience mental health problems. The UIN Jakarta Family Resilience Consultation Institute (LK3) tries to present a spiritual approach to addressing mental health problems faced by College students. So that there is a research formulation in the form of a spiritual approach like what is used by LK3 UIN Jakarta in overcoming mental health problems for College students.  This research will use qualitative research techniques with descriptive research types to provide an overview of the spiritual approach to handling College student mental health problems after the pandemic at UIN Jakarta LK3. This study also uses bibliography studies, observations, and interviews to dig deeper into the spiritual approach provided by LK3 in dealing with mental health problems in College students. The research results obtained were that during the pandemic there was a spike in mental health cases experienced by College students, especially on the problem of adaptation to the learning process. Similar to the post-pandemic period, mental health problems were experienced by College students in terms of learning adaptation issues. LK3 UIN Jakarta tries to use a spiritual approach to overcoming mental health problems in College students. This spiritual approach is carried out in several ways, namely aspects of worship practice (Prayer Fulfillment), Belief in life (Universality), and responsibility for one's life (Relationship).